2020
DOI: 10.1080/23723556.2020.1796179
|View full text |Cite
|
Sign up to set email alerts
|

Ser 784 phosphorylation: a clinically relevant enhancer of VCP function in the DNA damage response

Abstract: Valosin-containing protein (VCP) is essential for proteostasis during many cellular processes. However, it remains uncertain how its diverse functions are selectively regulated. We recently showed that DNA damage-induced Ser 784 phosphorylation specifically increases VCP function for the DNA damage response and significantly influences the survival of chemotherapy-treated breast cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…First, our cell line and patient data suggested that pSer 784 -VCP instead of total VCP levels predict PDAC response to genotoxic chemotherapies. This is conceptually consistent with the pleiotropic effects of VCP on global proteostasis [13][14][15]54] and the specific activating effect of Ser 784 phosphorylation on DDR function of VCP [25,26]. As with our prior study using surgical breast tumor samples [25], the PDAC TMA used in this study was constructed using tumor samples collected at surgery before adjuvant chemotherapies given to nearly all patients.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…First, our cell line and patient data suggested that pSer 784 -VCP instead of total VCP levels predict PDAC response to genotoxic chemotherapies. This is conceptually consistent with the pleiotropic effects of VCP on global proteostasis [13][14][15]54] and the specific activating effect of Ser 784 phosphorylation on DDR function of VCP [25,26]. As with our prior study using surgical breast tumor samples [25], the PDAC TMA used in this study was constructed using tumor samples collected at surgery before adjuvant chemotherapies given to nearly all patients.…”
Section: Discussionsupporting
confidence: 71%
“…VCP is phosphorylated at Ser 784 in its C-terminal tail by the PIKK kinases (ATM/ATR/DNA-PK) in response to different genotoxic insults [22][23][24]. However, the functional importance of Ser 784 phosphorylation remained unknown until our recent study [25,26]. Using an isogenic knockdown and rescue approach, we demonstrated that Ser 784 phosphorylation of VCP is essential for chromatin-associated protein degradation, DNA repair, checkpoint signaling, and cellular survival in response to diverse genotoxic chemotherapeutic treatments.…”
Section: Introductionmentioning
confidence: 99%
“…From a clinical perspective, the authors associated nuclear pSer784-VCP levels with poor outcomes for patients with triple-negative breast cancer receiving chemotherapy but not with other types of therapy, suggesting that pSer784-VCP might be a potential predictive biomarker for the efficacy of chemotherapy [ 79 ]. Subsequently, the same authors maintained that low levels of pSer784-VCP should be considered a predictive biomarker for patients with breast cancer who are treated with genotoxic therapies and that patients with higher levels of pSer784-VCP might benefit from chemosensitization DDR kinase family inhibitors already in clinical use [ 80 ].…”
Section: Vcp/p97 Expression and Function In Cancermentioning
confidence: 99%
“…Thus, VCP/p97 represents a potential prognostic biomarker and a therapeutic target. [71] Gastric cancer greater tumor size, presence of vascular and lymphatic invasion, lymph node metastasis, and shorter overall and disease free survival [72] cell survival, degradation of cellular regulators, and gastric carcinogenesis [73,74] low levels of CHOP and DR5 [75] Esophageal cancer higher frequencies of lymph node metastasis, deeper invasion, metastasis, and shorter disease free and overall survival [76] shorter overall survival [77] Breast cancer shorter overall survival [78] poor outcomes of triple-negative patients receiving chemotherapy [79,80] Hematological cancer tumor grade, stage, histological subtype, recurrence and shorter overall and disease-free survival of patients with B-cell lymphoma [104] multiple myeloma development and progression [105] poor prednisone responders in pediatric patients with acute lymphoblastic leukemia [106] exosome generation and secretion in Jurkat tumor cells [107] Melanoma advanced radiotherapy [108] immune escape [109] Glioblastoma radiosensitivity of glioblastoma cells, and survival time of xenografted mice with radiation treatment [110,111] HDAC6 levels and temozolomide resistance therapy [112] Ovarian cancer chemotherapy response in patients receiving the platinum-taxane combination [113] Testicular cancer development of different types of human testicular tumors [114] Bladder cancer shorter survival following bladder removal by cystectomy [115] Squamous cell carcinoma development of squamous cell carcinoma [116] 3.1. VCP/p97 in Gastrointestinal Cancers 3.1.1.…”
Section: Vcp/p97 Expression and Function In Cancermentioning
confidence: 99%
“…Mutations at codon 470 and 616 in the D1-D2 linker region that are associated with ATPase hyperactivity are resistant to VCP inhibitors [ 139 ]. Phosphorylation of C-terminal serine 784 activates the VCP DNA damage response [ 140 , 141 , 142 , 143 ]. The recruitment of VCP to double stranded DNA breaks relies on the VCP cofactors UFD1-NPL4 [ 144 ].…”
Section: Roles Of Vcp In the Nucleusmentioning
confidence: 99%